“We turned big rocks into little rocks”: a phenomenological study of the experience of college students who participated in a Spanish service-learning community program as freshmen - Courbou, Angélique (Kansas State University, 2021)
Although becoming more common, research on first-year programs for college students that combine several high-impact practices (HIP) are assessed at the institutional level, but not always published in peer-reviewed journals (Andrade, 2007). Research is being conducted, albeit mostly quantitatively, regarding individual HIP (e.g., impact of freshmen seminars on retention, benefits of study abroad), but little research has been devoted to multi-HIP programs (e.g., study abroad + service learning, learning communities + freshmen seminar). Following a constructivist approach, a descriptive phenomenological study was conducted to uncover the essence of the experience of having participated in a multi-HIP program (integrating learning community, service learning and faculty-led study abroad) at a large Midwestern public four-year institution. Fourteen participants, purposefully sampled, recounted their experience, through in-depth interviews and written reflections. The analysis of the data revealed five different yet related themes, evolving in parallel throughout the program. The first two revolved around the sense of community, while the last three centered on what the participants learned about service learning, themselves, and college. Unique to this study was the richness of the data which allowed to more comprehensively explain how the sense of community was built throughout the program, using Szreter and Woolcock’s (2004) concepts of bonding, bridging and linking, and McCabe’s (2016a, 2016b) work on friendship networks. Furthermore, as this multi-HIP program offered two meaningful group service-learning projects spaced out throughout the program, the data collected enabled a comparison of each activity using Engeström (2001)’s Expended Activity Theory Model. As more programs integrate various HIPs, the results of this qualitative study, focused on how students experience such programs, in conjunction with other existing research can assist institutions of higher education in evaluating current programs and designing new ones.
Keywords: Phenomenology; High-impact practices; Service learning; Learning community; Faculty-led study abroadHigher education